Pripovedna umetnost in terapevtsko samospoznanje - Küplen, Mojca (Analiza: časopis za kritično misel, 2023)
Narrative Art and Therapeutic Self-knowledge In recent years, there have been debates in aesthetics and philosophy of art on the question of whether we can acquire knowledge about the world from works of art. However, little has been written about the effects of art on cultivating self-knowledge and self-development. While, for most of us, it seems obvious that art has these effects, little is known about how and why these effects occur. Addressing this issue is the main aim of this paper. The gist of the argument is that narrative art provides a unique opportunity to adopt a dual (first- and third-personal) perspective on the self, which has been argued recently by psychologists and philosophers of mind to be necessary for obtaining the kind of self-knowledge that leads to self-development and self-change, i.e., therapeutic self-knowledge.